2010
DOI: 10.1016/j.ccr.2010.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitotic Exit Leads to Tumor Regression In Vivo: Modulation by Cdk1, Mastl, and the PP2A/B55α,δ Phosphatase

Abstract: Targeting mitotic exit has been recently proposed as a relevant therapeutic approach against cancer. By using genetically engineered mice, we show that the APC/C cofactor Cdc20 is essential for anaphase onset in vivo in embryonic or adult cells, including progenitor/stem cells. Ablation of Cdc20 results in efficient regression of aggressive tumors, whereas current mitotic drugs display limited effects. Yet, Cdc20 null cells can exit from mitosis upon inactivation of Cdk1 and the kinase Mastl (Greatwall). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
200
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 194 publications
(217 citation statements)
references
References 51 publications
12
200
0
5
Order By: Relevance
“…We have recently demonstrated that impairing cyclin B1 degradation in vivo by genetic elimination of Cdc20 is much more efficient in killing tumor cells than targeting the spindle assembly with classical poisons or new drugs inhibiting Eg5 or Plk1. 70 These observations are in agreement with the pioneer results using RNA interference (RNAi) against Cdc20 or expressing a non-degradable mutant of cyclin B1 in several tumor cell lines. 71 Whereas classical antimitotic drugs (vincristine or taxol) and new available mitotic inhibitors against Plk1 or kinesin Eg5 (BI2536 or monastrol, respectively) only induce a partial response in aggressive tumors, Cdc20 ablation results in complete metaphase arrest, leading to massive apoptotic cell death and complete tumor elimination in vivo.…”
Section: Cell Deathsupporting
confidence: 81%
See 4 more Smart Citations
“…We have recently demonstrated that impairing cyclin B1 degradation in vivo by genetic elimination of Cdc20 is much more efficient in killing tumor cells than targeting the spindle assembly with classical poisons or new drugs inhibiting Eg5 or Plk1. 70 These observations are in agreement with the pioneer results using RNA interference (RNAi) against Cdc20 or expressing a non-degradable mutant of cyclin B1 in several tumor cell lines. 71 Whereas classical antimitotic drugs (vincristine or taxol) and new available mitotic inhibitors against Plk1 or kinesin Eg5 (BI2536 or monastrol, respectively) only induce a partial response in aggressive tumors, Cdc20 ablation results in complete metaphase arrest, leading to massive apoptotic cell death and complete tumor elimination in vivo.…”
Section: Cell Deathsupporting
confidence: 81%
“…71 Whereas classical antimitotic drugs (vincristine or taxol) and new available mitotic inhibitors against Plk1 or kinesin Eg5 (BI2536 or monastrol, respectively) only induce a partial response in aggressive tumors, Cdc20 ablation results in complete metaphase arrest, leading to massive apoptotic cell death and complete tumor elimination in vivo. 70 Importantly, mitotic exit inhibition also affects pRb-null, p53-null or SAC-deficient cells, 70,71 suggesting widespread uses. In vitro, Cdc20-null tumor cells cannot escape from the metaphase arrest and die of mitotic cell death in 6-30 h. 70 Altogether, these results suggest that drugs that target Cdc20 or other components involved in cyclin B1 degradation, such as core components of the APC/C or the proteasome, could be quite effective in killing tumor cells.…”
Section: Cell Deathmentioning
confidence: 99%
See 3 more Smart Citations